Hungarian Monitoring, 16 November 1988 . [Magyar rádiófigyelő], 1988. november 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports on the Estonian parliament session - Report on demonstrations held in the US and Canada against Romanian human rights abuses - Article in Moskovskie Novosti on planned reform of the Soviet military - Wałęsa willing to conduct television interview with official trade union president - French opinion on acknowledgment of the new Palestinian state - A Soviet group protests against Romanian village destructions Domestic Affairs: - Reports on Károly Grósz's Madrid schedule - Rezső Nyers held the ceremonial speech at Karl Marx University of Economics jubilee council sitting - A parliamentary representative's opinion on holding the planned Budapest-Vienna World Exposition - Mátyás Szűrös talks at Szombathely activists' meeting on the multi-party system, errors made by the Party - Committee formed alongside Central Committee to re-examine constitution - Press report on event held at Jurta Theater to commemorate anniversary of the Brasov workers' movement - Anti-doping decision passed at World Association of Weightlifters' meeting in Budapest Economy: -The Industrial Committee of the Parliament discussed economy policy tasks for next year, including business profit tax - Opinions in Traders and Hospitality National Representation Association (KISOSZ) on the planned business profit tax - Interview with Ferenc Morvai about over-taxation impairing enterpreneurship and damaging national economy Külpolitika: - Jelentések az észt parlament üléséről - Jelentés a az emberi jogok romániai megsértése ellen rendezett Egyesült Államokbeli és kanadai tüntetésről - Cikk a Moszkovszkije Novosztiban a szovjet hadsereg tervezett reformjáról - Wałęsa hajlandó TV vitát folytatni a hivatalos szakszervezet elnökével - Francia álláspont az új palesztin állam elismerésével kapcsolatban - Egy szovjet csoportosulás tiltakozása a romániai falurombolás ellen Belpolitika: - Tudósítások Grósz Károly madridi programjáról - Nyers Rezső tartotta az ünnepi beszédet a Marx Károly Közgazdasági egyetem jubileumi tanácsülésén - Egy képviselő véleménye a tervezett Budapest-Bécs világkiállítás megrendezéséről - Szűrös Mátyás a többpárti rendszerről, a párt hibáiról is beszélt Szombathelyen az aktíva értekezleten - A Központi Bizottság mellett bizottság alakult az alkotmány felülvizsgálatára - Beszámoló a lapokban a brassói munkásmegmozdulás évfordulóján a Jurta Színházban rendezett rendezvényről - Dopping ellenes határozatot hozott a Súlyemelő Világszövetség budapesti ülése Gazdaság: - Az Országgyűlés ipari bizottsága a jövő évi gazdaságpolitikai feladatokról, ezen belül a vállalkozási nyereségadóról tárgyalt - A KISOSZ vélemények a vállalkozási nyereségadó tervezetről - Beszélgetés Morvai Ferenc vállalkozóval arról, hogy a túlzott adóztatás tönkretesz minden vállalkozást, minden vállalkozói kedvet és árt a népgazdaságnak is